SIGI LAMO DAN TINGGALAN SEJARAH ISLAM DI TERNATE - Pinem, Masmedia (Profetika Jurnal Studi Islam, 2013)
This study seeks to reveal the history ofthe ancient mosques in the city of Ternate.Through historical-archaeological-approaches, ancient mosques are described comprehensively.From the research of Sigi Lamo (Great Mosque) of the Ternate Sultanates, there are severalpoints found, first, Ternate Sultanates Sigi Lamo I sthe oldest mosque inTernate were builtaround the year 1606A Dat the time of Sultan Hamzah (1628-1648). Second, in terms oflayout Ternate Sultanate Sigi Lamo is very different with the mosques in Java?where themosqueis always adjacent to the palace, the square, and the market?. However, from thearchitecture aspects it?s showed the Javanese influences such as in the mosque polesor supportingpillars of the pyramidal roof, with asharps slope similar to the construction of Javanese house,wide of the porchis same to the main prayer hall. On eachsides ofthe Sultanates mosques, onthe top roof there is a window. In the west of mosque there isalso the sultanate family cemetery.Third, worshipat Ternate Sultanate Sigi Lamo arranged by a hereafter representative whichrepresented each ethnic orregional in Ternate. The here after representative (bobato akhirat)consists of Jiko Imam, Imam Java, Imam Sangaji, and Imam Moti. The four priests were onduty by turn seach week to organize worships at the mosque of Sultanates.Key words: history, archaeology, Ternate Sultanates mosque, hereafter bobatoPenelitian ini berupaya mengungkap sejarah masjid kuno di kota Ternate. Lewatpendekatan historis-arkeologis, masjid kuno dideskripsikan secara komprehensif. Dari hasilpenelitian terhadap Sigi Lamo (Masjid Agung) Kesultanan Ternate, beberapa poin yangdiungkapkan yaitu, pertama, Sigi Lamo Kesultanan Ternate merupakan masjid tertua diTernate yang didirikan sekitar tahun 1606 M pada masa Sultan Hamzah (1628-1648).Kedua, dari segi letak Sigi Lamo Kesultanan Ternate sangat berbeda dengan masjid yangada di Jawa?di mana masjid selalu berdekatan dengan kraton, alun-alun, dan pasar?.Namun, dari aspek arsitektur terlihat ada pengaruh Jawa seperti adanya tiang penyanggadi dalam masjid atau saka guru sebagai penyangga atap yang piramidal, dengan kemiringantajam mirip dengan konstruksi tajug, lebar serambi selebar unit ruang utama salat. Padasetiap sisi masjid Sultan, atap puncaknya dibuat jendela atap. Di barat masjid terdapatjuga komplek pemakaman keluarga sultan. Ketiga, peribadatan di Sigi Lamo KesultananTernate, diatur berdasarkan bobato akhirat yang mewakili dari masing-masing etnis ataudaerah yang ada di Ternate. Bobato akhirat tersebut terdiri dari Imam Jiko, Imam Jawa,Imam Sangaji, dan Imam Moti.Keempat imam inilah bertugas secara bergantian setiapminggunya untuk mengatur peribadatan di Masjid Sultan.Kata kunci: sejarah, arkeologi, masjid Kesultanan Ternate, bobato akhirat